Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I wonder how to solve this equation: $$\frac{\tan(x+20^{\circ })-\sin(x+20^{\circ })}{\tan(x+20^{\circ })+\sin(x+20^{\circ })}=4\sin^{2}\left(\frac{x}{2}+10^{\circ }\right)$$ in an elegant/shorter way. My way: $$\frac{\sin(x+20^{\circ })-\sin(x+20^{\circ })\cdot cos(x+20^{\circ})}{\sin(x+20^{\circ })+\sin(x+20^{\circ })\cdot \cos(x+20^{\circ})}=2[1-(\cos(x+20^{\circ}))]$$ so $$1-\cos(x+20^{\circ})=2[1-\cos(x+20^{\circ})][1+\cos(x+20^{\circ})]$$ which gives $$\cos(x+20^{\circ})=1\Rightarrow x=-20^{\circ}+360^{\circ}k\\\cos(x+20^{\circ})=-0.5\Rightarrow x=140^{\circ}+360^{\circ}k,\, \, x=-100^{\circ}+360^{\circ}k$$ Thanks.

share|improve this question

3 Answers 3

up vote 0 down vote accepted

Setting $\displaystyle\frac x2+10^\circ=y\iff x+20^\circ=2y$

$$\frac{\tan2y-\sin2y}{\tan2y+\sin2y}=\frac{\sin2y\cdot\dfrac{1-\cos2y}{\cos2y}}{\sin2y\cdot\dfrac{1+\cos2y}{\cos2y}}=\frac{\cos2y\sin2y(1-\cos2y)}{\cos2y\sin2y(1+\cos2y)}=\tan^2y$$ if $\cos2y\sin2y\ne0$

Now $\cos2y\sin2y=0\iff\sin4y=2\sin2y\cos2y=0\implies4y=n\cdot180^\circ$ where $n$ is any integer

So, we need $\displaystyle y\ne n\cdot45^\circ\ \ \ \ (1)$ and we have $\displaystyle\tan^2y=4\sin^2y,$

$\displaystyle\implies\sin^2y=4\sin^2y\cos^2y\iff\sin^2y(1-4\cos^2y)=0$

If $\displaystyle\sin^2y=0,\sin y=0\implies y=m\cdot180^\circ$ which is inadmissible by $(1)$

So, $\displaystyle1-4\cos^2y=0\iff\cos^2y=\frac14\iff\cos2y=2\cos^2y-1=-\frac12=\cos120^\circ$

$\displaystyle\implies2y=360^\circ\cdot r\pm120^\circ\iff y=180^\circ\cdot r\pm60^\circ$ where $r$ is any integer

So, $x=2y-20=\cdots$

share|improve this answer
    
@aric, How about this? –  lab bhattacharjee May 12 at 6:54
    
can you please check my answer? –  shaurya gupta May 12 at 7:22
    
@shauryagupta, I think you proceed a little further to discard the inadmissible value –  lab bhattacharjee May 12 at 12:48
    
@labbhattacharjee - so $x=2y-20^\circ=-20^\circ+360^\circ\cdot r\pm120^\circ$? –  aric May 12 at 21:42
    
@aric, Any doubt? Please validate the values –  lab bhattacharjee May 13 at 2:47

$$\frac{\tan(x+20^{\circ })-\sin(x+20^{\circ })}{\tan(x+20^{\circ })+\sin(x+20^{\circ })}=\\\frac{\frac{\sin(x+20^{\circ })}{\cos(x+20^{\circ })}-\sin(x+20^{\circ })}{\frac{\sin(x+20^{\circ })}{\cos(x+20^{\circ })}+\sin(x+20^{\circ })}=\\\frac{\sin(x+20^{\circ })}{\sin(x+20^{\circ })}\frac{\frac{1}{\cos(x+20^{\circ })}-1}{\frac{1}{\cos(x+20^{\circ })}+1}=\\\frac{\sin(x+20^{\circ })}{\sin(x+20^{\circ })}\frac{\cos(x+20^{\circ })}{\cos(x+20^{\circ })}\frac{1-\cos(x+20^{\circ })}{1+\cos(x+20^{\circ })}=\\\frac{\tan(x+20^{\circ })}{\tan(x+20^{\circ })}\frac{2\sin^2(\frac{x}{2}+10^{\circ })}{2\cos^2(\frac{x}{2}+10^{\circ })}=\\\frac{\tan(x+20^{\circ })}{\tan(x+20^{\circ })}\tan^2\left(\frac{x}{2}+10^{\circ }\right)$$ Thus you can rewrite $$\frac{\tan(x+20^{\circ })-\sin(x+20^{\circ })}{\tan(x+20^{\circ })+\sin(x+20^{\circ })}=4\sin^{2}\left(\frac{x}{2}+10^{\circ }\right)$$ as $$\frac{\tan(x+20^{\circ })}{\tan(x+20^{\circ })}\tan^2\left(\frac{x}{2}+10^{\circ }\right)=4\sin^{2}\left(\frac{x}{2}+10^{\circ }\right)\\\frac{\tan(x+20^{\circ })}{\tan(x+20^{\circ })}\frac{1}{\cos^2(\frac{x}{2}+10^{\circ })}=\frac{4}{\cos^2(\frac{x}{2}+10^{\circ })}\\\frac{\tan(x+20^{\circ })}{\cos^2(\frac{x}{2}+10^{\circ })}=\frac{4\tan(x+20^{\circ })}{\cos^2(\frac{x}{2}+10^{\circ })}\\\frac{3\tan(x+20^{\circ })}{\cos^2(\frac{x}{2}+10^{\circ })}=0\Rightarrow\\\tan(x+20^{\circ })=0\\x+20^{\circ }=0^{\circ }\\x=-20^{\circ }+k\pi^{\circ }\qquad k\in\Bbb{Z}$$

share|improve this answer
    
why is $4sin^{2}(\frac{x}{2}+10^{\circ})=\frac{4}{cos^{2}(\frac{x}{2}+10^{\circ})}$ –  aric May 11 at 18:55
    
@Foga- also you got: $1=4$ so i think something is wrong in your solution. –  aric May 11 at 19:08
    
Nothing! You obtain $1=4$ by dividing by $0$... –  Foga May 11 at 19:39
    
@Foga, But $x=180^\circ n-20^\circ$ will make the LHS $\dfrac00$ –  lab bhattacharjee May 12 at 6:55
    
I've edited the answer to make as clear as possible... –  Foga May 12 at 11:09

$4sin^2(\frac{x + 20^\circ}2) = 4\cdot1/2\cdot(1-\cos(x+20^\circ)) = 2-2\cos(x+20^\circ)$

Applying componendo and dividendo on $\frac{tg(x+20^{\circ })-sin(x+20^{\circ })}{tg(x+20^{\circ })+sin(x+20^{\circ })}=4sin^{2}(\frac{x}{2}+10^{\circ })$ ,

$-\sec(x+20^\circ) = \frac{2-2\cos(x+20^\circ)+1}{2-2\cos(x+20^\circ) -1}$, $cos(x+20^\circ)\ne1/2$
$-\sec(x+20^\circ)\cdot(1-{2\cos(x+20^\circ)}) = {3-2\cos(x+20^\circ)}$
$-\sec(x+20^\circ)+2=3-2\cos(x+20^\circ)$
$2cos(x+20^\circ)-\sec(x+20^\circ)-1=0$
$2cos^2(x+20^\circ)-cos(x+20^\circ)-1=0$
Can you solve it further?

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.